2014
DOI: 10.1002/jrs.4488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gypsum and anhydrite ground layers in 15th and 16th centuries Portuguese paintings by Raman Spectroscopy and other techniques

Abstract: The purpose of this work is to characterize Portuguese painting ground layers from the 15th and 16th centuries (1450–1600), focusing particularly on the Coimbra, Lisbon, and Viseu workshops. Calcium sulfate, used regularly in these layers is common in the Iberian Peninsula as a natural resource. Its use is now confirmed, as already studied in Spanish paintings, and it was prepared generally by addition of animal glue. Besides the common esthetic language to the various painting workshops at the time, chalk/cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Other recent investigations on paintings include: a 17th century Japanese painting (Quattrini et al), altarpieces and painting workshops of 15th and 16th centuries from Viseu, Coimbra, Lisboa and Évora (Antunes et al). Edwards et al found chrome yellow, synthesized in 1809, in limited zones of ‘The Malatesta’ painting, most probably a result of a 19th century retouching.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent investigations on paintings include: a 17th century Japanese painting (Quattrini et al), altarpieces and painting workshops of 15th and 16th centuries from Viseu, Coimbra, Lisboa and Évora (Antunes et al). Edwards et al found chrome yellow, synthesized in 1809, in limited zones of ‘The Malatesta’ painting, most probably a result of a 19th century retouching.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary Portuguese painters and, in general, the painters of the South used grounds mainly of gypsum. 25 In Portuguese collections of art, there are many Flemish paintings, as well as paintings which reveal in their features the Flemish influences, mostly of them produced in the first half of the sixteenth century, partly as a result of the intense political and commercial exchanges that existed between the two countries. 26 Many paintings were imported from Flanders, others were produced in Portugal by artists who travelled from Flanders to carry out painting commission and then returned to their country of origin.…”
Section: R Es Ult S and Discussionmentioning
confidence: 99%
“…According to the hue, thickness, particle size, and material composition of each layer, the decorative parts were classified into 3 sections, i.e., the surface lacquer layers, Gypsum is not only a white pigment commonly used in ancient wall paintings and polychrome cultural relics [22,23] but also a gel material that was used for architectural decoration in ancient China [24,25].…”
Section: Lacquering Techniquementioning
confidence: 99%